Loess–paleosol carbonate clumped isotope record of late Pleistocene–Holocene climate change in the Palouse region, Washington State, USA. Issue 2 (5th July 2018) - Lechler, Alex R.; Huntington, Katharine W.; Breecker, Daniel O.; Sweeney, Mark R.; Schauer, Andrew J.
Abstract: The Channeled Scabland–Palouse region of the Pacific Northwest (PNW) of the United States preserves geomorphic and pedosedimentary records that inform understanding of late Pleistocene–Holocene paleoclimate change in a region proximal to the last glacial period Cordilleran Ice Sheet. We present a clumped (Δ47 ) and conventional (δ 18 O, δ 13 C) isotopic study of Palouse loess–paleosol carbonates in combination with carbonate radiocarbon ( 14 C) dating to provide new measures of regional late–last glacial (~31–20 cal ka BP) and Holocene soil conditions. Average clumped isotope temperatures (T(Δ47 )) for last glacial Palouse loess–paleosol carbonates (9±4°C) are significantly lower than those for Holocene-aged carbonates (T(Δ47 )=18±2°C) in study sections. Calculated soil water δ 18 OVSMOW values (−16±2‰) for last glacial carbonates are also offset relative to those for Holocene-aged samples (−11±1‰), whereas calculated soil CO2 δ 13 CVPDB values are similar for the Holocene (−16.9±0.2‰) and late–last glacial (−16.7±1.1‰) periods. Together, these paleoclimate metrics indicate late–last glacial conditions of pedogenic carbonate formation in the C3 grassland soils of the Palouse were measurably colder (9±5°C) than during the Holocene and potentially reflect a more arid last glacial paleoclimate across the Palouse, findings in agreement with previous proxy studies and climate model simulations for the region.